2017
DOI: 10.1097/ta.0000000000001537
|View full text |Cite
|
Sign up to set email alerts
|

Severe trauma and chronic stress activates extramedullary erythropoiesis

Abstract: Background Severe traumatic injury is associated with bone marrow dysfunction that manifests as impaired erythropoiesis and prolonged hematopoietic progenitor cell (HPC) mobilization from the bone marrow. Extramedullary erythropoiesis, the development of red blood cells outside the bone marrow, has not been studied following severe injury and critical illness. This study examined the influence of lung contusion/hemorrhagic shock (LCHS) followed by chronic stress (CS) on the rodent spleen and to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 32 publications
5
30
1
Order By: Relevance
“…We also found that that Meg-01 cells undergo active chemotaxis towards common inflammatory stimuli 35 and can migrate through channels with cross section smaller than 50 μm 2 . This size is comparable to that of small capillary vessels our observation raises the possibility that MKs are not ‘trapped’ in microcirculatory beds, but instead they may move through and diapedese into surrounding tissues where they participate in inflammation and regeneration 3,47–51 . Additionally, the observed directional budding of platelets into the channels containing the chemotactic agent and “obstruction” of the channels by MKs and platelets and/or vesicles, suggest an ability to contribute to decreased blood flow within small capillary vessels 10,43,5255 .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We also found that that Meg-01 cells undergo active chemotaxis towards common inflammatory stimuli 35 and can migrate through channels with cross section smaller than 50 μm 2 . This size is comparable to that of small capillary vessels our observation raises the possibility that MKs are not ‘trapped’ in microcirculatory beds, but instead they may move through and diapedese into surrounding tissues where they participate in inflammation and regeneration 3,47–51 . Additionally, the observed directional budding of platelets into the channels containing the chemotactic agent and “obstruction” of the channels by MKs and platelets and/or vesicles, suggest an ability to contribute to decreased blood flow within small capillary vessels 10,43,5255 .…”
Section: Discussionmentioning
confidence: 55%
“…Megakaryocytes (MKs) are commonly recognized as key participants in hemostatic processes through the production of platelets 12 . In addition to their presence in the bone marrow, MKs can also be located in the lungs, lymph nodes, spleen, and liver during extra medullary hematopoiesis 37 . MKs have also been reported to be significantly increased in the lungs during severe pulmonary inflammation, such as acute respiratory distress syndrome (ARDS), when they are believed to promote inflammation via the release of platelets 810 .…”
mentioning
confidence: 99%
“…19,20 Dysfunctional erythropoiesis in a rodent trauma model can be ameliorated with chemical sympathectomy using either propranolol or clonidine, suggesting that a reduction of hypercatecholaminemia improves erythropoiesis. [11][12][13][21][22][23][24][25][26] Prior research has evaluated the postinjury inflammatory state in severely injured trauma patients and demonstrated their erythropoietic dysfunction and iron dysregulation. 27 To validate our preclinical findings and to expand upon our prior study of the postinjury inflammatory state in humans, the purpose of this study was to evaluate additional severely injured trauma patients and determine if there is a relationship between the ISS in trauma patients, and the degree of neuroendocrine activation and systemic inflammation that is related with persistent injury-associated anemia as well as to further characterize the bone marrow response to injury.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence, however, is increasing that, under specific stress situations, erythropoiesis can also take place outside the bone marrow. This stress or extramedullary erythropoiesis has been reported to occur in several organs, particularly in the spleen, of mice and even humans [20,[28][29][30][31]. Previously, the spleen was found to be a site of increased erythropoiesis in P. chabaudi-resistant C57BL/6 mice [32].…”
mentioning
confidence: 96%